2022
DOI: 10.1186/s12916-022-02325-0
|View full text |Cite
|
Sign up to set email alerts
|

The association of neurodevelopmental abnormalities, congenital heart and renal defects in a tuberous sclerosis complex patient cohort

Abstract: Background Tuberous sclerosis complex (TSC) is a rare multi-system genetic disorder characterised by the presence of benign tumours throughout multiple organs including the brain, kidneys, heart, liver, eyes, lungs and skin, in addition to neurological and neuropsychiatric complications. Intracardiac tumour (rhabdomyoma), neurodevelopmental disorders (NDDs) and kidney disorders (KD) are common manifestations of TSC and have been linked with TSC1 and TSC2 loss-of-function mutations independently… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 62 publications
(75 reference statements)
0
2
0
Order By: Relevance
“…Also, the small group did not allow a comparison between TSC1 and TSC2 patients, in terms of the affected regions or clinical manifestations. Quantitative MR-derived indices like total brain volume and tuber volume were shown to be different between patients with TSC1 and TSC2 mutations in previous studies ( Ogórek et al, 2020 , Robinson et al, 2022 ), therefore, it would be interesting to observe these groups with advanced diffusion-derived indices. Another limitation is the wide age range of the study group.…”
Section: Discussionmentioning
confidence: 91%
“…Also, the small group did not allow a comparison between TSC1 and TSC2 patients, in terms of the affected regions or clinical manifestations. Quantitative MR-derived indices like total brain volume and tuber volume were shown to be different between patients with TSC1 and TSC2 mutations in previous studies ( Ogórek et al, 2020 , Robinson et al, 2022 ), therefore, it would be interesting to observe these groups with advanced diffusion-derived indices. Another limitation is the wide age range of the study group.…”
Section: Discussionmentioning
confidence: 91%
“…C H D i s o f t e n a s s o c i a t e d w i t h o t h e r neurodevelopmental disabilities (NDD) and genetic or syndromic conditions (4,5): 10% of children with CHD and 50% of those with severe CHD also have NDD (6). Epidemiological studies suggest that environmental or genetic factors are involved in the causation of approximately 20-30% of CHD cases, while other unexplained CHD with NDD cases are believed to have a multifactorial causation (7). In recent years, an increasing number of studies have identified single-gene variants that are closely related to CHD.…”
Section: Introductionmentioning
confidence: 99%